The strategic application of information technology in health care organizations / John P. Glaser, Claudia Salzberg. - Glaser, John P. (John Patrick), 1955- (Jossey-Bass, 2011)
"Thoroughly revised and updated, this book offers a comprehensive resource for understanding information technology (IT) strategic planning and implementation within healthcare institutions. Filled with illustrations and case studies, the book is written for leaders and high-level managers in healthcare organizations. New to this edition are updated concepts and practices, more illustrative examples of strategy as well as updated industry data and technology examples. The book also contains news chapters on IT asset and IT-centric organizational attributes and value and offers learning objectives, key terms, and discussions questions in each chapter."--Provided by publisher.